Seni bina Islam : satu tarikan pelancongan - Mohd Nawawi, Norwina (IKIM, 2007)
The influence of Islamic faith in the built environment of the Malay world was gradual and intrinsically integrated into the culture of the Malay people who are simple and adaptable. Islam did not command any immediate change to the existing architecture but built up the people's aqidah on oneness of God, that indirectly influence the ritual of construction, planning and decorations.Through literature review, observations and personal experience as an architect and researcher of the Malay built environment to Islam, this article explore the meaning of Islamic Architecture and how, hypothetically through physical evidence, underlines the salient changes adopted in the architecture today.